2008
DOI: 10.1002/cphc.200700475
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembling Nanoparticles at Surfaces and Interfaces

Abstract: Nanoparticles are the focus of much attention due to their astonishing properties and numerous possibilities for applications in nanotechnology. For realising versatile functions, assembly of nanoparticles in regular patterns on surfaces and at interfaces is required. Assembling nanoparticles generates new nanostructures, which have unforeseen collective, intrinsic physical properties. These properties can be exploited for multipurpose applications in nanoelectronics, spintronics, sensors, etc. This review sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
359
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(368 citation statements)
references
References 437 publications
3
359
0
6
Order By: Relevance
“…To date, a few reviews have discussed nanoparticle superlattices,1, 2, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 however, a dedicated review emphasizing the important roles of soft ligands has not yet reported to the best of our knowledge. We therefore are motivated to cover the recent advances in nanoparticle superlattices from viewpoint of soft ligands.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few reviews have discussed nanoparticle superlattices,1, 2, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 however, a dedicated review emphasizing the important roles of soft ligands has not yet reported to the best of our knowledge. We therefore are motivated to cover the recent advances in nanoparticle superlattices from viewpoint of soft ligands.…”
Section: Introductionmentioning
confidence: 99%
“…1 These NCs can self-assemble in a range of different two-dimensional ͑2D͒ and three-dimensional ͑3D͒ superstructures. [2][3][4][5] NCs are usually protected by an organic capping layer that prevents aggregation, e.g., gold NCs are often capped with alkyl thiol molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The following parameters were used in the calculation. For semiconducting CdSe nanoparticle we take into account only most prominent long-wavelength exciton transition with resonant wavelength λ 01 = 590 nm that corresponds to ω 10 , the linewidth ∆λ 1 = 3 nm, the radius R 1 = 5 nm and squared magnitude of electric dipole moment of the transition |P 12 | 2 1 = 1.91 · 10 −31 erg·cm 3 [7,8]. For silver nanoparticle corresponding values are λ 02 = 420 nm, ∆λ 12 = 90 nm, R 2 = 6 nm and |P 12 | 2 2 = 3.12 · 10 −3 erg·cm 3 [29].…”
Section: One Metallic and One Semiconductor Particlesmentioning
confidence: 99%
“…These phenomena allow the formation of extremely complicated structures without using any technological processes. One should note that the majority of studies devoted to self-organized nanostructures formation is based on the chemical interactions and employs selective interactions between molecules from which the nanostructures are to be formed [4][5][6][7][8]. It seems promising to use physical fields, laser radiation in particular, for controlled self-organization of nanoobjects into clusters.…”
Section: Introductionmentioning
confidence: 99%